Impacts of alternative investment scenarios - Kim, Soonho; Cenacchi, Nicola; Wiebe, Keith D.; Sulser, Timothy B.; Dunston, Shahnila; Vos, Rob; Dimaranan, Betina; Allen, Summer L.; Rice, Brendan; Gustafson, Sara (International Food Policy Research Institute, 2019)
The International Model for Policy Analysis of Agricultural Commodities and Trade (IMPACT) explores policies that can help feed the world, reduce poverty, and protect the natural resource base. Here we examine how alternative investment scenarios affect agricultural production, productivity, and food security for the period 2010-2050 compared to a reference scenario. These results are drawn from a recent report that provides a quantitative assessment of the impacts of alternative investment options on the CGIAR’s objectives relating to poverty, food and nutrition security, and natural resources and ecosystem services in the context of changes in population, income, technology, and climate to 2050 (Rosegrant et al. 2017). The report was developed in collaboration with scientists from all 15 CGIAR Centers and was intended to inform decision-making by the CGIAR and its partners in relation to agricultural research and development.